2001
DOI: 10.1046/j.1525-1497.2001.016006376.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic use in ontario facilities that provide chronic care

Abstract: Antibiotic use is frequent and highly variable amongst patients who receive chronic care. Reducing antibiotic prescriptions for asymptomatic bacteriuria represents an important way to optimize antibiotic use in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
122
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(133 citation statements)
references
References 35 publications
7
122
3
Order By: Relevance
“…When compared with published criteria, 41% of case patients received antibiotic treatment despite never meeting McGeer criteria. This percentage is higher than the findings by Loeb et al, 20 who reported that 30% of patients with asymptomatic bacteriuria received antibiotics. This inappropriate treatment was not without consequence because patients who received antibiotics without meeting McGeer criteria were 8 times more likely to develop C difficile in logistic regression than the NH population.…”
Section: Commentcontrasting
confidence: 62%
“…When compared with published criteria, 41% of case patients received antibiotic treatment despite never meeting McGeer criteria. This percentage is higher than the findings by Loeb et al, 20 who reported that 30% of patients with asymptomatic bacteriuria received antibiotics. This inappropriate treatment was not without consequence because patients who received antibiotics without meeting McGeer criteria were 8 times more likely to develop C difficile in logistic regression than the NH population.…”
Section: Commentcontrasting
confidence: 62%
“…The incidence of antibiotic use varies considerably, with 50-80% of residents receiving at least an antibiotic course per year [4,7,8]. There is substantial facility-level variation in antibiotic-prescribing incidence (at least five-to ten-fold) [7,9,10], which may partly explain the differences seen in the European-wide study of nursing homesbetween six defined daily doses per 1000 residents per day in Germany to 136 defined daily doses per 1000 residents per day in Northern Ireland [11]. A recent systematic review showed that antibiotics are most frequently prescribed for urinary tract infections (32-66%), respiratory tract infections (15-36%) and skin and soft tissue infections (13-18%) [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, antibiotics are often prescribed for residents with bacteriuria but no clear signs and symptoms of UTI. Among patients with reported urinary tract infections, Loeb et al found that 30 % were treated for asymptomatic bacteriuria [41]. In residents with no sign or symptoms of a UTI, cultures are sometimes collected due to pressure from nursing home staff, physicians, or resident family and during annual check-ups [26].…”
Section: Treating Suspected Utismentioning
confidence: 99%
“…Risk factors for UTIs with a MDRO include catheter use, previous hospitalization, and prior antimicrobial use [44,45]. Fluoroquinolones are frequently prescribed for UTIs [14,41]. However, resistance to fluoroquinolones among isolates collected from nursing home residents was reported in 1998-2003, suggesting resistance is likely to remain a problem today [46].…”
Section: Consequences Of Unnecessary Antimicrobial Usementioning
confidence: 99%